Treatment with 2,4-Dihydroxybenzoic Acid Prevents FSGS Progression and Renal Fibrosis in Podocyte-Specific Coq6 Knockout Mice - Widmeier, Eugen; Airik, Merlin; Hugo, Hannah; Schapiro, David; Wedel, Johannes; Ghosh, Chandra C; Nakayama, Makiko; Schneider, Ronen; Awad, Agape M; Nag, Anish; Cho, Jang; Schueler, Markus; et al. (Journal of the American Society of Nephrology, 2019)
Although studies have identified >55 genes as causing steroid-resistant nephrotic syndrome (SRNS) and localized its pathogenesis to glomerular podocytes, the disease mechanisms of SRNS remain largely enigmatic. We recently reported that individuals with mutations in COQ6, a coenzyme Q (also called CoQ , CoQ, or ubiquinone) biosynthesis pathway enzyme, develop SRNS with sensorineural deafness, and demonstrated the beneficial effect of CoQ for maintenace of kidney function. To study function in podocytes, we generated a podocyte-specific knockout mouse ( ) model and a transient siRNA-based knockdown in a human podocyte cell line. Mice were monitored for development of proteinuria and assessed for development of glomerular sclerosis. Using a podocyte migration assay, we compared motility in knockdown podocytes and control podocytes. We also randomly assigned 5-month-old mice and controls to receive no treatment or 2,4-dihydroxybenzoic acid (2,4-diHB), an analog of a CoQ precursor molecule that is classified as a food additive by health authorities in Europe and the United States. Abrogation of in mouse podocytes caused FSGS and proteinuria (>46-fold increases in albuminuria). studies revealed an impaired podocyte migration rate in knockdown human podocytes. Treating mice or cells with 2,4-diHB prevented renal dysfunction and reversed podocyte migration rate impairment. Survival of mice given 2,4diHB was comparable to that of control mice and significantly higher than that of untreated mice, half of which died by 10 months of age. These findings reveal a potential novel treatment strategy for those cases of human nephrotic syndrome that are caused by a primary dysfunction in the CoQ biosynthesis pathway.